Analysis of Inhibiting Factors in the Micro Business Credit Financing Process and Implications for Customer Business Sustainability at Bank Syariah Indonesia Mukomuko Branch Office - Ayu Retno Trianingsih; Idwal B; Esti Alfiah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
This study aims to determine and analyze the implementation process of Sharia People's Business Credit (KUR Syariah) distribution, identify inhibiting factors in the financing process, and analyze the implications of these obstacles on the business sustainability of customers at Bank Syariah Indonesia (BSI) KCP Mukomuko. The research method used is qualitative with a descriptive approach. Data were collected through in-depth interviews with five informants consisting of the Micro Business Manager (MBS) and Retail Sales Executive (RSE), as well as through observation and documentation. The results showed that the distribution process of KUR Syariah at BSI KCP Mukomuko is carried out through stages of application, OJK SLIK file verification, field survey (On The Spot), 5C feasibility analysis (Character, Capacity, Capital, Collateral, Condition), to the signing of the murabahah contract. The main inhibiting factors found include internal factors in the form of technical and geographical constraints, as well as external factors such as the unreadiness of customer administrative documents and the low quality of the character or capacity of prospective debtors. The implications of these financing process obstacles impact delays in receiving capital which cause customers to lose business momentum; however, in general, successfully distributed financing provides positive implications for increasing turnover, adding assets, and expanding market reach for MSMEs in Mukomuko Regency. Keywords: KUR Syariah, Inhibiting Factors, Business Sustainability, BSI KCP Mukomuko.